Pengaruh Pelatihan Teknologi Informasi Dan Implementasi E-Government Terhadap Produktifitas Kerja Pegawai Di Badan Pengusahaan Batam - sasa ani arnomo (Universitas Putera Batam, 2014)
In a change from developing countries to developed countries requires a great effort by the government. With that goal the government to make changes in the system of government that is implementing the E -Government. Accelerate the process of procedures, transparency of information and ease of access to information as the purpose of this implementation. E-government is in need of some new information technologies as a support system. With the use of new information technology then there are some government employees who are less mastered for operationalizing. So the government provided training for these problems. Place the training of government officials called the IT Center. With the background of the research carried out to determine how the effect of E-Government and IT Center to Work Employee Productivity Results. E-Government measurement variables are informativeness, Information Format, Easy of Use, Timeliness, measurement Reliability. Variabel IT Center ( IT Training Center ) is Intsruktur, modules, training results. While the measurement variables for employee productivity is Job Performance, Initiative, Cooperation, Responsibility, Honesty.